Effects of carbon‐coated titanium dioxide nanoparticles as a photostabilizer on the photodegradation of rigid poly(vinyl chloride). Issue 9 (10th December 2013) - Sokhandani, Parvane; Abdi, Mohammad Adel; Ghaebi Mehmandoust, Shadi; Babaluo, Ali Akbar; Mehdizadeh, Reza; Rezaei, Mostafa; Rakhshani, Masoud
ABSTRACT In this study, nanocomposites of rigid poly(vinyl chloride) (UPVC) using the synthesized carbon‐coated titanium dioxide (TiO2) nanoparticles and commercial powder of titanium dioxide (with rutile structure) were prepared by melt blending. The presence of carbon‐coated TiO2 nanoparticles with rutile structure in UPVC matrix led to an improvement in photo stability of UPVC nanocomposites in comparison with commercial UPVC. The photocatalytic degradation behavior of nanocomposites was investigated by measuring their structural changes, surface tension, and mechanical and morphological properties before and after UV exposure for 700 h. It was found that mechanical and physical properties of UPVC nanocomposites are not considerably reduced after UV exposure in the presence of carbon‐coated TiO2 nanoparticles even in small percentage of nanoparticles in comparison with the presence of commercial TiO2 particles. Therefore, it can be concluded that UPVC/TiO2 nanocomposite with low content of carbon‐coated TiO2 nanoparticles(0.25 wt %) illustrated high stability under light exposure. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40228.